Neutrophil-lymphocyte ratio and fournier gangrene severity index are not prognostic factors of mortality in fournier gangrene patients - Raizandha, Muhammad Achdiar; Hidayatullah, Furqan; Kloping, Yudhistira Pradnyan; Rizaldi, Fikri (Faculty of Medicine, Universitas Trisakti, 2022)
Background Fournier gangrene (FG) is a life-threatening disease, commonly found in diabetic and immunocompromised patients. Recent studies suggested the use of new parameters apart from the commonly used Fournier gangrene severity index (FGSI), such as the neutrophil-lymphocyte ratio (NLR), the clinical use of which remains questionable. Therefore, we aimed to evaluate the role of the NLR and FGSI as a prognostic factor of mortality in patients with FG. MethodsThis is an analytical study with a retrospective approach involving 109 adult patients diagnosed with FG. Data were collected regarding medical history, symptoms, physical examination findings, and laboratory tests. The FGSI score and NLR were determined. Bivariate analysis was performed using chi-square test and independent t-test. Overall survival between groups was compared using Kaplan–Meier survival estimates and Cox regression test. ResultsOf the 109 patients, 90 survived (82.5%, group 1) and 19 died (17.43%, group 2). The cut-off point of NLR among the patients was 10.9, with a 73.7% sensitivity and 60% specificity. The area under curve value was 0.65 (95% CI; 0.524-0.754; p<0.05). The Kaplan Meier survival analysis showed that NLR was as an independent prognostic factor of mortality in FG patients (HR 5.177; 95% CI; 1.092-8.471; p<0.05), but Cox regression analysis showed that NLR and FGSI were not significant prognostic factors of mortality (p=0.09 and p=0.179; respectively). ConclusionThis study demonstrated that NLR and FGSI are not important as prognostic tools for FG mortality.